Economic system of Malay community: Self sufficiency to commersial economic level. - Subramaniam, Vijayaletchumy; Dani, Noor Aina; Wan Mohammad, Wan Muna Ruzanna (2011)
This paper discusses the economic system of Malay community from self-sufficiency to commercial level. Since the beginning of 19th century until 1963, the economic system in Malaysia can be categorised into 2 main categories; self-sufficiency economic system and commercial economic system. The pattern and manner of the economic system at that time followed exactly the system imposed by the ruler. Malay traditional economic system was different from the economic system brought by the British. The Malays based their economics on the self-sufficiency sytem. The purpose of this system was to support the family’s daily needs. Majority of these Malay communities lived by the riverside and at the remote areas. They planted paddy. When the British came and conquered Malaya, the self-sufficiency system was changed to the economic commercial from the aspect of planting, technology, and marketing. Now at the 21st century, Malays have transformed themselves systematically in this economic sector parallel to the world’s every need. The pattern of today’s economic is more commercialised with the help of the sophisticated technology. Nevertheless, being Malays, there are some of the communities who still cling to the self-sufficiency system as their hobby. With the existence of the sophisticated technology in agriculture, the economic opportunities are getting higher and the marketing needs have started demanding on new things to be marketed.